Assessing Inequality Using Percentile Shares. (June 2016) - Jann, Ben
At least since Thomas Piketty's best-selling Capital in the Twenty-First Century (2014, Cambridge, MA: The Belknap Press), percentile shares have become a popular approach for analyzing distributional inequalities. In their work on the development of top incomes, Piketty and collaborators typically report top-percentage shares, using varying percentages as thresholds (top 10%, top 1%, top 0.1%, etc.). However, analysis of percentile shares at other positions in the distribution may also be of interest. In this article, I present a new command, pshare, that estimates percentile shares from individual-level data and displays the results using histograms or stacked bar charts.